PENGARUH UKURAN KAP, KEPEMILIKAN MANAJERIAL DAN KARAKTERISTIK DEWAN KOMISARIS TERHADAP PENGUNGKAPAN TATA KELOLA PERUSAHAAN - Maulidina Alyssa Makarima; Totok Dewayanto (Diponegoro Journal of Accounting, 2019)
Not only the practice of good corporate governance is needed within companies, the disclosure of the practice itself is also an essential aspect behind a company's success or failure. The aim of this study is to examine the factors that are likely to affect corporate governance disclosure. Aside from the dependent and independent variables, this study uses market capitalization as a control variable. The population used in this study is public companies listed in Indonesia Stock Exchange for the period of 2016 - 2017. Sample is taken using purposive sampling method, amounting total 152 companies as samples. The hypotheses are tested using multiple linear regression analysis. The results are as follows; board independence has a significant and positive effect on corporate governance disclosure, managerial ownership and board age have significant and negative effect on corporate governance disclosure, on the other hand audit firm size and board size have no significant effect on corporate governance disclosure.